2022
DOI: 10.1111/mec.16664
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and clonal diversity in floating aquatic plants: Comparative genomic analysis of water hyacinth species in their native range

Abstract: Many eukaryotic organisms, including fungi, protozoa, invertebrates, algae and land plants, have mixed reproductive strategies multiplying by sexual and asexual reproduction. The commonest form of asexual reproduction in angiosperms is vegetative propagation, also referred to as simply clonal growth (Harper, 1977). Approximately 80% of flowering plants have some form of clonal propagation (Klimes et al., 1997) in which vegetative shoots (ramets) are produced by the parental genotype (genet) during growth. Clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…However, the distance and frequency of their dispersal in aquatic plants are poorly understood (Li, 2014). A genomic study of Eichhornia crassipes in its native range revealed long-distance and interbasin dispersals of vegetative propagules (up to 1500 km) (Cunha et al, 2022), which confirmed the hypothesis of high clonal dispersibility in free-floating aquatic plants (Sculthorpe, 1967). However, our study suggests that long-distance and interbasin dispersals of vegetative propagules (up to 1041 km) also occur in emergent aquatic plants.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…However, the distance and frequency of their dispersal in aquatic plants are poorly understood (Li, 2014). A genomic study of Eichhornia crassipes in its native range revealed long-distance and interbasin dispersals of vegetative propagules (up to 1500 km) (Cunha et al, 2022), which confirmed the hypothesis of high clonal dispersibility in free-floating aquatic plants (Sculthorpe, 1967). However, our study suggests that long-distance and interbasin dispersals of vegetative propagules (up to 1041 km) also occur in emergent aquatic plants.…”
Section: Discussionmentioning
confidence: 86%
“…Among four basic aquatic life forms, free-floating and floating-leaved aquatic plants were supposed to have higher dispersibility of vegetative propagules (Sculthorpe, 1967). A recent study using genomic data verified the effective long-distance and interbasin dispersal of vegetative propagules in floating leaved Eichhornia azurea (up to 185 km) and free-floating E. crassipes (up to 1500 km) in central South America, the native range of both species (Cunha et al, 2022). However, genomic analyses at large scales are lacking in emergent and submerged aquatic plants, which are essential to measuring the magnitude of vegetative propagule dispersal in emergent and submerged species.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sequence data obtained from the Hiseq X Ten platform were processed for SNPs identification using the GBS pipeline integrated within Stacks 3.0.166 [ 56 ]. In brief, variants were filtered using Vcftools 0.1.14 [ 57 ] based on criteria such as a minimum depth of coverage (> 5), quality score (> 30), and an initial maximum missingness of 50% [ 58 ]. Subsequently, the dataset was examined to ensure that no samples exhibited high levels of missingness (all samples were found to have less than 30% missing data).…”
Section: Methodsmentioning
confidence: 99%
“…Hence the pattern of isolation by distance widely expected among sexual populations should be much weaker among asexual populations. This prediction has rarely been tested, with mixed results (da Cunha et al 2022;Guillemeinet al 2008).…”
Section: Introductionmentioning
confidence: 99%